2022
DOI: 10.1097/rct.0000000000001376
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors for Air Embolism in Computed Tomography Fluoroscopy–Guided Biopsy of Lung Tumor With the Use of Noncoaxial Automatic Needle

Abstract: The aim of the study is to analyze incidence and risk factors for air embolism during computed tomography (CT) fluoroscopy-guided lung biopsies using noncoaxial automatic needle.Materials and Methods: Between February 2014 and December 2019, 204 CT fluoroscopy-guided lung biopsies (127 men; mean age, 70.6 years) using noncoaxial automatic needle under inspiratory breath holding were performed. We retrospectively evaluated the incidence of air embolism as presence of air in the systemic circulation on whole-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Several risk factors for fistula formation have been identified in previous studies, including the length of the needle path through the ventilated lung, the depth of needle penetration into the nodule, and the number of biopsy samples obtained ( 33 , 34 ). A recent study found a higher radiological incidence of air embolism of 3.92%, which was unexpectedly higher than that reported in previous research; however, it should be mentioned that many of the detected cases were asymptomatic, and only 0.98% of patients experienced symptoms related to air embolization ( 35 ). In our study, no cases of air embolism were detected in either the ICG group or the hook-wire group.…”
Section: Discussionmentioning
confidence: 73%
“…Several risk factors for fistula formation have been identified in previous studies, including the length of the needle path through the ventilated lung, the depth of needle penetration into the nodule, and the number of biopsy samples obtained ( 33 , 34 ). A recent study found a higher radiological incidence of air embolism of 3.92%, which was unexpectedly higher than that reported in previous research; however, it should be mentioned that many of the detected cases were asymptomatic, and only 0.98% of patients experienced symptoms related to air embolization ( 35 ). In our study, no cases of air embolism were detected in either the ICG group or the hook-wire group.…”
Section: Discussionmentioning
confidence: 73%
“…Air bubbles may enter the pulmonary veins by the accidental placement of the needle tip within a pulmonary vein, followed by air injection into the needle; another mechanism consists in the creation of a fistula between a bronchus and an adjacent pulmonary vein by the inadvertent placement of the needle through both structures, allowing passage of air into the pulmonary vein. It’s not difficult to understand these mechanisms considering that pulmonary vein pressure is normally around 10 cmH2O [ 12 ].…”
Section: Discussionmentioning
confidence: 99%